Implementasi Pengenalan Jenis Pola Tapak Ban (Tread) Menggunakan Metode Local Binary Patterns - Ambrosius Sitompul (Universitas Budi Darma, 2020)
The rapid development in the field of technology now makes matters easier, one of which is in the field of image processing, image processing has become a trend in the field of multimedia communication including the automotive industry. By doing image processing we can use the information contained in an image snapshot. In this study utilizing digital image processing technology for the introduction of each type of tire, tire condition is one of the important aspects of car eligibility standards, and standards that exist in Indonesia and are currently a bit neglected, this is thought to be one of the causes of accidents in Indonesia. Currently the existing tire feasibility test system is carried out by utilizing human power but humans have limitations